Combined Tai Chi and cognitive interventions for older adults with or without cognitive impairment: A meta-analysis and systematic review. (August 2022) - Li, Fei; Wang, Li; Qin, Yan; Liu, Guiying
Abstract: Background and purpose: Evidence from the field of cognitive interventions indicates that nonpharmaceutical interventions seem more promising in enhancing cognition. The number of clinical trials that examine the cognitive benefits of combined physical exercise with cognitive intervention on older adults has recently increased. Tai Chi (TC) has been recommended as an effective and safe exercise for older adults aged 60 and over. However, there is a lack of conclusion about whether combined TC with cognitive interventions can show more benefits than a single intervention for older adults. Thus, this review aimed to evaluate the effects of combined TC and cognitive interventions on older adults. Methods: PubMed, Embase, PsycINFO, and Web of Science were searched for English peer-reviewed papers from inception until November 12, 2021. Data were extracted by two independent reviewers. Results: A total of 1524 records were generated and nine studies were included. The pooled results showed that combined TC and cognitive interventions showed significantly large gains on memory [standardised mean difference (SMD) = 0.87, 95% confidence interval (CI): (0.01, 1.74), P 0.05], moderate gains on cognition [SMD = 0.74, 95% CI:(0.19, 1.29), P 0.05], and small size effects on balance. No statistically significant difference was found in executive function, depression, risk of falls, or well-being. Conclusion: Combined TC and cognitive interventions have positive effects on improving cognition and balance in older adults, but their superiority over the single intervention, as well as their additional effects on the physical and psychological function, are required further investigation. Highlights: Combined Tai Chi and cognitive interventions have moderate to large effects on improving global cognition and memory for older adults. Small effects of combined Tai Chi and cognitive interventions were found on balance. No effects were reported on executive function, depressive symptoms, risks of falls, or wellbeing. The superiority of combined Tai Chi and cognitive interventions over the single intervention requires further investigation.